Agricultura familiar e informalidade: o seu papel no abastecimento local de alimentos - Silveira, Laurício Bighelini da (2013)
This thesis presents a proposition about a method of study and analysis regarding informality in the local supply created by the marketing of surplus consumption and commercial production of diversified family farming. It was created due to the lack of a similar specific method to study this particular type of phenomenon, namely the presence of informality in the local supply in small urban areas. The concern with the rural exodus, with the consequent change in the relationship rural/urban, as well as the analysis of the importance of these activities of these families having the option to choose or not to remain in their place of origin and its influence on a possible local development integrating rural/urban, were the guiding factors in this study. Thus, it is relevant to prove its existence and evaluate its importance. The used methodology was based on the proposed method giving its methodological procedures, which consist of the following four steps: Stage I - formal data collection of secondary data on the study area, the Regional Development Council of Valley Jaguari (CVJ), typifying the municipalities and choosing the municipality of Mata to proceed this study (a small typical cluster family farm); Stage II - primary data collection, socioeconomic, consumption habits, role of suppliers, using proper form with the sample of households; Stage III data collection through a mini census with the local trade using a proper form of data identification, products sold and their suppliers, and their positions, and Stage IV - held by the sample family producers listed in stages II and III, collected with the use of a specific form their socioeconomic data, productive purposes and their positions. Data analyses showed the predominance of the existence of product consumption in informal households, either by its own production, by donation and the informal trade of surplus products of self-consumption of local family farming, which occurs in a direct way regarding producer/consumer, prevailing a relationship based on trust between the involved parties. The presence of local trade as an informal intermediary was proved to be tenuous. The informal activities have shown to be influential in providing the power to those family farmers to choose to remain or not in its original place. It is concluded that the proposed method is efficient and promising for the study and analysis of informality in the local supply in small urban areas, which is derived mainly through the surplus of self-consumption of the family farming.